دراسة تحليلية لبعض العوامل المؤثرة على نوعية الحياة في إحدى القرى الجديدة بمحافظة البحيرة - الفيل، خالد توفيق محمد; عبدالحليم، علي محمود (جامعة المنصورة - كلية الزراعة, 2020)
This search aimed mainly investigate the level of quality of life in a village in new land. Also, we want to know the lack of social services in the village and there impacts on the growers and the quality of life as a hole. Data were collected from 186 respondents (beneficiaries) from EL-Adl village in new lands in Western Nubaria in Abo EL-Matamir district. Systematic random sample is implemented. This study tested 17 independent variables which variety between nominal, ordinal and interval. The analysis of data was resulted that the level of quality of life is medium but sometime is high. The village had not sufficient social services like sanitation, agricultural extension service, vet. Service and banking service. An analytical study through chi-square pointed to that one independent (graduated certificate) variable had significant relationship with the level of quality of life while Multiple Step Wise Regression pointed to four variables (the lack of social services, invention soul, age and leadership degree) had significant relationship with the level of quality of life. Four independent variables explained 30.9% of variation of the level of quality of life, only the lack of social services explained 23.5% of variation of the level of quality of life.
يهدف هذا البحث إلى التعرف على مستوى نوعية الحياة داخل إحدى القرى الجديدة، ومدى توفر بعض الخدمات الاجتماعية وتأثير ذلك على نوعية وجودة الحياة فيها. وقد أجري البحث على عينة من المزارعين المنتفعين (186 منتفع) من قرية العدل التابعة للوحدة المحلية لقرية أبو بكر الصديق التابعة لمركز أبو المطامير بمحافظة البحيرة. وقد أسفرت نتائج البحث أن مستوى نوعية الحياة داخل القرية متوسط ويميل قليلا إلى المستوى الأعلى، كما أن هناك العديد من الخدمات الناقصة داخل القرية مثل الصرف الصحي والإرشاد الزراعي والخدمة البيطرية وخدمات الائتمان الزراعي. كما أسفرت نتائج تحليل مربع كاي والانحدار التدرجي المتعدد Multiple Step Wise Regression أن متغيرات: المؤهل الدراسي، مدى توفر الخدمات الاجتماعية بالقرية، الروح الابتكارية، السن، درجة القيادية هم المتغيرات المؤثرة على نوعية الحياة داخل القرية، وأن المتغيرات الأربع الأخيرة ساهمت في تفسير 30.9% من التباين الحادث في مستوى نوعية الحياة داخل المجتمع وكان نصيب متغير مدى توفر الخدمات الاجتماعية بالقرية 23.5%.
Keywords: الخدمات الاجتماعية -- جودة الحياة -- التنمية الريفية -- مصر